1999
DOI: 10.1523/jneurosci.19-19-08464.1999
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9/Gelatinase B Is Required for Process Outgrowth by Oligodendrocytes

Abstract: Oligodendrocytes (OLs) extend processes to contact axons as a prerequisite step in myelin formation. As the OL processes migrate toward their axonal targets, they modify adhesion to their substrate, an event that may be regulated by matrix metalloproteinases (MMPs). In the mouse optic nerve, MMP-9/gelatinase B increases during myelin formation. Although tissue inhibitor of metalloproteinase (TIMP)-3 also increases in parallel, the developing optic nerve has focally active MMPs demonstrable by in situ zymograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
218
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 254 publications
(232 citation statements)
references
References 60 publications
12
218
1
1
Order By: Relevance
“…In particular, oligodendrocyte-derived MMP-9 supports oligodendrogliosis and myelin restoration (Uhm et al 1998;Oh et al 1999;Larsen et al 2003). We previously demonstrated that MPTP treatment of both mice and monkeys induces a prominent oligodendrogliosis concomitant to the inflammatory process here described (Annese et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…In particular, oligodendrocyte-derived MMP-9 supports oligodendrogliosis and myelin restoration (Uhm et al 1998;Oh et al 1999;Larsen et al 2003). We previously demonstrated that MPTP treatment of both mice and monkeys induces a prominent oligodendrogliosis concomitant to the inflammatory process here described (Annese et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…Goat anti-mouse antibody conjugated to Cy-3 (Jackson ImmunoResearch) was used as the secondary antibody to detect labeled OLs. Mouse OLs extend several thread-like processes from soma, which facilitated the counting of the percentage of O1-positive cells with processes (Oh et al, 1999). The number of cells exhibiting processes at 24 hr was measured after treatment with the conditioned medium from bone marrow-derived macrophages (BMDM) from A1AR ϩ/ϩ or A1AR Ϫ/Ϫ .…”
Section: Methodsmentioning
confidence: 99%
“…It employs fluorescein isothiocyanate-labeled DQ™-gelatin, (Molecular Probes, Eugene, OR), a substrate for gelatinolytic MMPs, which emits a fluorescent signal when cleaved (45). Unfixed sections of tissue prepared by cryostat were incubated overnight at 37°C with reaction buffer (0.05 M Tris-HCl, 0.15 M NaCl, 5 mM CaCl 2 , and 0.2 mM NaN 3 , pH 7.6) containing 40 g/ml DQ™-gelatin.…”
Section: Methodsmentioning
confidence: 99%